Numerical modelling of the phytoplankton patterns in an upwelling event off the NW Iberian Margin - Rocha, Carlos (2018)
An extreme event in September 2007, presenting a strong upwelling core detaching from the Galician NW coast and extending towards west-northwest from the Cape Finisterre - Cape Ortegal zone, with the formation of several filaments and a consequent strong response in chlorophyll concentration values is analyzed. To do so, a NPZD biogeochemical module coupled to a ROMS_Agrif configuration is used. The model response was satisfactory and an analysis of the event, including its forcing, was made. The particular wind direction and intensity along with the specific coastal orientation of the study area were identified as important characteristics for the development of the event. The analysis of the behavior and evolution of this phytoplankton bloom may give further insight in the relations between atmospheric forcing, the consequent characteristic coastal ocean processes, and their conditioning in phytoplankton distribution and patterns in the study area.